Effects of eight interval training sessions in hypoxia on anaerobic, aerobic, and high intensity work capacity in endurance cyclists - Arezzolo, D.; Coffey, V. G.; Byrne, N. M.; Doering, T. M. (High Altitude Medicine & Biology, 2020)
Aim: This study aimed to determine if eight sessions of supramaximal but steady-state, set duration interval training in hypoxia enhanced measured anaerobic capacity and work performed during high intensity exercise.